(3CdajI GHf eGdc hTeS GdNdGUIs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3bGd eMeO gh GHf eGdc CMeO QHj Gddg NjQ eGdc s
(3BNQgG (B:s
(3hCMeO Gddg eUdjkG Ydi eMeO NjQ fHj oCQSdG GfJgJ HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B380 - (3U(B461s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B32 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B151s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI (B- (3GdQHGW (B(487 (3O(B) s
Keywords: (3GdfMhs